Упростите выражение (x+y)+(y-x) (a-b)-(a-b) (c-d)-(c+d) (u-+v)-(v-u) m-(n-p-m) (a+b)-(b+c)-(a-c) (k+m)-(k-m)+(m-k) (b+1)-(a-1)-(b-a)

2

Ответы и объяснения

2012-11-05T09:48:20+04:00

(х+у)+(у-х)=х+у+у-х=2у

(а-в)-(а-в)=а-в-а+в=0

(с-д)-(с+д)=с-д-с-д=-2д

(u+v)-(v-u)=u+v-v+u=2u

m-(n-p-m)=m-n+p+m=2m-n+p

(a+b)-(b+c)- (a-c)=a+b-b-c-a+c=0

(k+m)+(m-k)+(m-k)=k+m+m-k+m-k=3m-k

(b+1)-(a-1)-(b-a)=b+1-a+1-b+a=2

2012-11-05T10:19:02+04:00

х+у)+(у-х)=х+у+у-х=2у

(а-в)-(а-в)=а-в-а+в=0

(с-д)-(с+д)=с-д-с-д=-2д

(u+v)-(v-u)=u+v-v+u=2u

m-(n-p-m)=m-n+p+m=2m-n+p

(a+b)-(b+c)- (a-c)=a+b-b-c-a+c=0

(k+m)+(m-k)+(m-k)=k+m+m-k+m-k=3m-k

(b+1)-(a-1)-(b-a)=b+1-a+1-b+a=2